From Postmodernism to the Anthropocene. Baptisms of an age without a name - Benedetti, Carla (Itinerari, 2023)
It is only a few years since the word “Anthropocene” has entered the common language, after being for a long time the exclusive domain of the scientific community. It is now progressively adopted in the humanities as the proper name of our age. This is in itself a rather extraordinary fact: it is the first time that a term used in geology is chosen over a cultural term as a definition of the age we live in. Over the past two centuries, the names that baptized the current epoch, modernism, postmodernism, came from art, architecture, sociology or philosophy; but to name this new age that has succeeded the postmodern, the humanities have had to take their cue from the sciences. What has prevented humanist culture from exerting its customary baptismal right over the new epoch? What has inhibited the normal methods of historical periodization and the typically modern way in which the movement through History is represented? This essay investigates this new and curious sense of being lost in history and the way in which the humanities have repressed over the past decades the greatest emergency mankind has ever faced: the risk of its own extinction.